The Urgency of Media Literacy in Early Childhood in the Digital Age: A Review of a Literature Study - Aprida, Siti Nurul; Adawiyah, Robiatul; Kurnia, Lita; Mustaotinnah, Hasna (As-Sibyan: Jurnal Pendidikan Anak Usia Dini, 2026)
Massive exposure to digital media has created a complex environment for early childhood development, offering both learning opportunities and significant risks. In this context, media literacy emerges as a fundamental competency; however, gaps remain in developmentally appropriate implementation strategies and in building synergistic collaboration between parents and educators. This study aims to synthesize empirical evidence on the urgency of media literacy, implementation strategies, stakeholder roles, and challenges in fostering media literacy among children aged 0–8 years. Employing a systematic literature review guided by the PRISMA framework, this study analyzed peer-reviewed scientific articles published between 2019 and 2025. The findings reveal four major themes. First, media literacy functions as a form of “cognitive immunization” that supports the development of critical thinking, creativity, and digital resilience in early childhood. Second, parents and educators play a central role as key mediators, although their effectiveness is frequently constrained by a lack of alignment between practices in the home and school environments. Third, implementation strategies exist along a continuum, ranging from restrictive approaches to active mediation and empowerment through content creation. Fourth, systemic challenges persist, particularly the absence of formal curriculum integration and persistent inequities in access to digital resources. This study concludes that a paradigm shift from a passive, protective approach toward proactive empowerment is essential. The findings provide a strong conceptual foundation for policies and practices that integrate media literacy collaboratively and developmentally, to nurture critical and responsible digital citizens from an early age.